Surface layer slurry, silica sol shell and preparation method thereof
By using the composite and grading of angle quartz powder and spherical zircon powder in the surface layer slurry of silicon sol shell, combined with the use of modified quartz powder and polysaccharide solution, the existing surface layer slurry has solved the problem of high cost and difficult to meet the performance, and achieved high powder ratio, good coating performance and improved surface quality and breathability.
Patent Information
- Application Number
- CN202411695045.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-25
AI Technical Summary
The existing surface layer slurry is costly to achieve high powder ratio required raw materials, and it is difficult to meet the requirements of coating performance and surface quality at the same time.
By using the combination and grading of angle quartz powder and spherical zircon powder in the surface layer slurry, the viscosity of the silicon sol and the content of silica are adjusted, combined with the use of modified quartz powder and polysaccharide solution, the powder-liquid ratio and bonding performance are improved, and the amount of zircon powder is reduced.
It is achieved without affecting the coating and hanging performance, and improve the powder-liquid ratio and surface quality of the surface slurry, reduce production costs, and improve the breathability and mechanical properties of the silicon sol shell.
Smart Images

Figure BDA0005151893440000111 
Figure BDA0005151893440000201 
Figure BDA0005151893440000211
Abstract
Description
Technical Field
[0001] The invention relates to the field of silica sol shells, and in particular to a surface layer slurry, a silica sol shell and a preparation method thereof. Background Art
[0002] Silica sol shell is a high-performance shell material widely used in the field of precision casting. It is composed of refractory materials (such as quartz powder, alumina powder, etc.) and silica sol (a silicate solution), and is prepared by multi-layer coating and roasting processes. Silica sol shell has high strength, high density and good surface finish, which can meet the requirements of high-precision castings. At present, silica sol shells with high performance requirements often use zircon powder as refractory material, but the cost of zircon powder is relatively high, and quartz powder is difficult to achieve a high powder-to-material ratio. Therefore, there is an urgent need for a surface slurry with quartz powder as the main refractory material that can also ensure that the slurry reaches a high powder-to-material ratio. Summary of the invention
[0003] The object of the present invention is to provide a surface slurry for preparing a silica sol shell, so as to solve the problem that the raw material cost of the existing surface slurry is high in order to achieve a high powder-to-material ratio.
[0004] The present invention also aims to provide a method for preparing a silica sol shell, which can improve the air permeability of the surface layer shell mold and the bonding degree between the surface layer and the back layer.
[0005] The present invention also aims to provide a high-strength and high-refractory silica sol shell with quartz powder as the main refractory material.
[0006] The embodiments of the present invention are implemented by the following technical solutions:
[0007] A surface slurry for preparing a silica sol shell comprises, by weight, 8-12 parts of silica sol, 20-25 parts of angular quartz powder, and 5-8 parts of spherical zircon powder; the content of silicon dioxide in the silica sol is 23wt%-27wt%, the particle size of the angular quartz powder is 180-200 mesh, and the particle size of the spherical zircon powder is 270-350 mesh.
[0008] At present, in the investment casting industry, due to environmental issues, the water glass process is facing elimination, and is replaced by the silica sol-quartz sand and mullite sand composite shell making process. The surface layer of this process usually uses silica sol-quartz powder slurry and mullite sand.
[0009] The silica sol quartz sand shell making process is mainly used to manufacture metal parts. The process is to mix quartz sand with silica sol to form a refractory coating, and then make the outer shell (shell mold) of the casting model through a series of steps, and finally pour the molten metal into the shell mold to cool and solidify, so as to obtain the desired casting. The main steps of the silica sol quartz sand shell making process are as follows:
[0010] Preparing the pattern: First, a pattern is made according to the design of the required casting. The pattern is usually made of materials such as wood, plastic, metal or wax.
[0011] Coating: Apply a layer of high temperature resistant coating evenly on the surface of the mold. This step is to improve the surface quality and fire resistance of the shell mold.
[0012] Impregnation of silica sol-quartz sand mortar: Immerse the painted surface into the slurry to allow it to fully absorb the slurry to form a binder layer.
[0013] Sanding: After taking out the mold from the slurry solution, immediately sprinkle a layer of mullite sand on its surface. Mullite sand, as a refractory material, can withstand high temperatures without chemical changes.
[0014] Drying: The sanded mold needs to be placed in a well-ventilated environment to dry naturally, or placed in an oven for heating and drying to ensure that the silica sol is completely solidified and the refractory aggregate is firmly attached to the mold surface.
[0015] Repeated dipping and sanding: In order to increase the thickness and strength of the shell mold, the above steps of dipping slurry and sanding may need to be repeated several times, and drying should be carried out after each sanding.
[0016] Demolding: When the shell mold reaches sufficient thickness and strength, the internal pattern can be removed, leaving a hollow shell mold.
[0017] Firing: The shell mold needs to be fired at high temperature to further improve its strength and fire resistance, and also to remove any residual moisture or organic matter in the shell mold.
[0018] Pouring: Finally, pour the molten metal into the shell mold. After it cools and solidifies, break the shell mold to obtain the desired metal casting.
[0019] For the silica sol shell making process, to ensure that the casting has a good surface quality, the surface slurry must be able to evenly cover the surface of the wax mold, and at the same time, it must have a sufficient coating thickness so that sand particles cannot penetrate the coating. Therefore, it is necessary to control two important parameters of the surface slurry: slurry viscosity (η) and powder-liquid ratio (n).
[0020] The viscosity of the slurry is the consistency of the slurry. If it is too thick, it will affect the coating of the module. If it is too thin, the required coating thickness cannot be achieved. In principle, the maximum viscosity should be maintained without affecting the coating. When the slurry is measured by a standard flow cup for more than 40 seconds, it will affect the coating effect. The powder-liquid ratio refers to the ratio of powder to liquid in the slurry. The larger the powder-liquid ratio, the thicker the coating, the smaller the possibility of sanding penetrating the coating, and the better or more stable the surface quality of the casting.
[0021] For zircon powder coating, under the premise of ensuring that the viscosity of the slurry does not affect the coating, the powder-liquid ratio can easily reach more than 3.0, and the coating thickness can also reach more than 0.08mm, so the powder-liquid ratio and coating thickness are relatively ideal. However, for quartz powder coating, the powder-liquid ratio is difficult to exceed 1.8. If it is higher, the slurry will become viscous, which will seriously affect the coating. The coating thickness is also difficult to reach 0.06mm. In the production process, there may be a phenomenon of sanding and breaking through the coating, so the surface quality of the casting is difficult to achieve an ideal state.
[0022] Although the performance of zircon powder coating is better, the cost of zircon powder is much higher than that of quartz powder. The price of quartz powder with better quality is about 1,000-2,000 yuan / ton, while the price of zircon powder per ton is generally more than 10,000 yuan. Therefore, the applicant hopes to make the performance of quartz powder coating reach or approach the performance of zircon powder coating through process improvement, thereby greatly reducing production costs. The applicant considers whether it is possible to greatly reduce the amount of zircon powder by compounding the two, reduce economic costs and make the coating performance suitable for most castings. Since spherical quartz powder has a higher bulk density, better dispersibility and fluidity, it can reduce the viscosity of the system and reduce powder agglomeration. Therefore, the applicant initially used spherical quartz powder and zircon powder for compounding, but found that when the proportion of zircon powder in the powder is less than 50%, the powder-liquid ratio exceeds 2.0, which will affect the coating. Therefore, one of the core concepts of the present invention is how to further reduce the proportion of zircon powder without affecting the coating.
[0023] The applicant used 830 silica sol commonly used in the existing process as the basis, and added distilled water to reduce its overall viscosity, so that the amount of powder can be increased under the condition of a certain final viscosity. However, the reduction in bonding performance will affect the strength of the shell, so the silicon dioxide content in the silica sol specified in this case will not be too low.
[0024] In order to further increase the bonding performance, angular quartz powder and spherical zircon powder are compounded. The angular quartz powder has an irregular shape and a larger contact area with the binder, which can increase the bonding area between the angular quartz powder and the binder. However, the fluidity of the angular quartz powder is lower than that of the spherical quartz powder, and the fluidity will affect the powder-liquid ratio that this case wants to increase. Therefore, this case increases the particle size of the angular quartz powder and increases the gaps between the connected angular quartz powders, thereby reducing the mutual friction and obstruction between the quartz powders and reducing the fluidity. At the same time, using finer spherical zircon powder to fill the gaps can not only increase the density of the coating, thereby increasing its strength, but also further reduce the mutual obstruction and aggregation between the quartz powders, and increase fluidity and dispersibility. In addition, the irregular quartz powder is more in contact with the spherical zircon powder, and the contact between it and the spherical zircon powder is mainly point contact, so the use of spherical zircon powder will further increase the fluidity of the slurry. When the casting has high requirements for surface quality, the particle size of the powder in the surface slurry should not be too large, so the use of finer zircon powder can also improve the surface quality of the casting.
[0025] In theory, the above purpose can also be achieved by using angular zircon powder and spherical quartz powder, but the applicant found in the test process that when using angular zircon powder and spherical quartz powder, the powder-liquid ratio of the slurry is lower than the above solution at the same viscosity. The applicant guesses that one of the reasons is that this case hopes to increase the fluidity of the system by reducing the viscosity of the silica sol, but in order to compensate for the reduction in bonding performance, angular powder is used, and angular powder will essentially increase the viscosity of the system. Therefore, it is necessary to ensure that the fluidity of the slurry with the same powder-liquid ratio is increased after the effects of the two are offset. The change curve of the influence of the two on fluidity is irregular, so it is necessary to find a suitable balance point to increase the final fluidity. At this time, the ratio of angular powder to spherical powder and particle size grading are particularly important, otherwise the fluidity of the slurry may be reduced. When angular zircon powder and spherical quartz powder are used, the increase in fluidity after the effects of the above two powders offset each other is lower than that when angular stone powder and spherical zircon powder are used. Therefore, the applicant found during the test that it is difficult to meet the needs of fluidity and adhesion at the same time. When the fluidity meets the needs, the bonding degree between the powders is low due to the small amount of angular powder.
[0026] A method for preparing a silica sol shell, comprising:
[0027] S100, immersing the pattern into the surface layer slurry for hanging the pattern, and then sanding and drying to obtain the surface layer pattern; the surface layer slurry adopts the surface layer slurry;
[0028] S200, hanging the surface layer pattern in the back layer slurry, and then sanding and drying, after repeating for multiple times, to obtain a back layer shell mold;
[0029] S300, hanging the back layer shell mold in the sealing slurry, and demoulding after drying to obtain a primary shell mold;
[0030] S400, the primary shell mold is subjected to a calcination process to obtain a silica sol shell;
[0031] The surface layer is sanded with 80-100 mesh Mullite sand.
[0032] The pattern can be a wax pattern. Although a large amount of quartz powder is used in the surface slurry of the present invention, the thickness of the surface layer can still reach more than 0.075 mm, so that the coating is not easily penetrated when sanding, and the particle size of the mullite sand can be appropriately increased, and the gap between the mullite sands can be increased, which is convenient for the back layer slurry to penetrate into the surface coating, increase the bonding degree between the two, reduce the possibility of cracking during baking, and improve the mechanical properties and fire resistance of the shell.
[0033] Preferably, the S200 includes:
[0034] D100, the surface layer pattern is molded in the first back layer slurry, and then sanded and dried to obtain the first back layer pattern; the first back layer slurry comprises: 10-15 parts of 830 silica sol and 18-24 parts of spherical quartz powder; the particle size of the spherical quartz powder is 200-230 mesh, and 120-140 mesh mullite sand is used for sanding;
[0035] D200, the first back layer pattern is hung in the second back layer slurry, and then sanded and dried to obtain a back layer shell mold; the second back layer slurry includes: 10-15 parts of 1430 silica sol and 13-17 parts of spherical quartz powder; the particle size of the spherical quartz powder is 150-180 mesh, and 40-60 mesh mullite sand is used for sanding.
[0036] 830 silica sol refers to the silica sol with a particle size of 8nm and a mass concentration of 30%. Since the coating formed by the first back layer slurry is used to connect the surface layer coating and the coating formed by the second back layer slurry, its powder ratio is lower than that of the surface layer slurry, which facilitates the migration of the first back layer slurry to the surface layer coating. One of the purposes of selecting spherical quartz powder instead of zircon powder for the first back layer slurry is to reduce the thickness of the coating formed by the first back layer slurry. When sanding, the relatively smaller mullite sand partially penetrates the first back layer, and the end extends into the sanding layer of the surface layer, thereby improving the bonding degree of the two layers of coating. Under normal circumstances, in order to ensure the air permeability of the shell, the particle size of the back layer sanding will be higher than that of the surface layer. The reason why the particle size of the first back layer sanding can be smaller than that of the surface layer in this case is that the particle size of the mullite sand used for the surface layer sanding is higher than that of the conventional quartz powder slurry surface layer. Therefore, when sanding the first back layer, it seems that the particle size is smaller, but the difference is not large compared with the air permeability of the conventional back layer. In addition, since the particle size of the Mullite sand used when sanding the surface layer is relatively large, the density is reduced. When sanding the first back layer, the interlocking of the two sanding layers can improve the density and increase the shell strength.
[0037] The coating formed by the second backing slurry is used to connect the first backing layer and the sealing slurry layer. Its powder ratio is lower than that of the first backing slurry. At the same time, in order to ensure air permeability, reduce drying time, facilitate subsequent demoulding, and improve subsequent casting effects, the powder particle size and sand particle size are increased. In order to improve the strength of the shell, the second backing slurry can be applied repeatedly.
[0038] Preferably, the spherical quartz powder used in the first backing layer slurry is modified quartz powder, and the preparation steps of the modified quartz powder include: adding the spherical quartz powder to the polysaccharide solution and then obtaining the modified quartz powder by spray drying.
[0039] Coating the surface of quartz powder with polysaccharides can improve its dispersibility, so that the coating of the first back layer slurry can be better combined with the surface layer, and the structural strength of the shell can be improved. In addition, the decomposition of the coating layer during the roasting process can also increase the air permeability of the coating formed by the first back layer slurry, reducing the impact of the small particle size of the first back layer sand on the air permeability. One of the purposes of choosing physical coating instead of chemical coating is to reduce the decomposition problem of the coating layer.
[0040] Preferably, the mass concentration of the polysaccharide solution is 15%-20%, the polysaccharide includes one or more of chitosan, sodium alginate, cellulose, and cyclodextrin, and the mass ratio of spherical quartz powder to polysaccharide solution is 1:2-2:3.
[0041] On the premise that the quartz powder can be stably coated, the quartz powder is also required to be highly dispersed and stably suspended in the polysaccharide solution. Therefore, the mass concentration of the polysaccharide solution is limited in this case.
[0042] Preferably, the calcination process in S400 includes: firstly heating to 700-800°C at a rate of 10-20°C / min and keeping the temperature for 15-25min, and then heating to 950-1050°C at a rate of 25-30°C / min and keeping the temperature for 20-30min.
[0043] The main purpose of the roasting process is to remove moisture, residual mold material and volatiles, improve the high-temperature mechanical properties of the shell, and improve the air permeability and filling capacity of the shell. During the roasting process, attention should be paid to the cracking caused by the difference in shrinkage rate of each layer of the shell, especially the relatively thin surface layer. Therefore, it is necessary to control the initial heating rate. In this case, the powder of the back layer slurry is different from the surface layer, and the surface layer is heated before the back layer, so the temperature control requirement is higher. Under normal circumstances, after the shell is fully heated, due to the gradual increase in the particle size of the sanding layer and the particle size of each layer of powder, the moisture migration direction of the surface layer tends to the sealing layer, which will increase the difference in dryness between the surface layer and the remaining layers, and the shrinkage difference between the layers is large. In this case, the powder particle size of the first back layer and the particle size of the sanding layer between it and the second back layer are small, which relatively increases the proportion of moisture in the surface layer directly overflowing from the surface layer, and the dryness of the remaining layers is increased, thereby reducing the shrinkage difference between the surface layer and the remaining layers, and the surface layer is not easy to crack. After a period of heat preservation, the silica sol is sintered to form a porous structure. At this time, the bound water in the surface layer is more likely to overflow directly from the surface layer, so the sintering can continue after the temperature is raised. The strength and refractory properties of the shell are increased through high-temperature sintering.
[0044] Preferably, the drying conditions in S100 are: drying temperature of 20-25°C, relative humidity of 50%-60%, and drying time of 10-15h; the drying conditions in S200 are: drying temperature of 30-35°C, relative humidity of 30%-40%, and drying time of 6-8h.
[0045] The surface layer has a higher density and a higher requirement for smoothness, so the drying temperature is lower and the relative humidity is higher, so as to ensure that the drying speed of each part of the surface layer is consistent as much as possible to avoid cracking of the surface layer shell. Since the back layer is located in the middle of the shell, the smoothness requirement is lower than that of the surface layer, so the drying temperature is relatively high and the relative humidity is low. In the process of shell preparation, most of the time is used to dry the slurry of each layer, so shortening the drying time can greatly improve the process efficiency. The drying time is closely related to air permeability. Good air permeability is conducive to the migration of water vapor. The back layer shell of the present invention has good air permeability, so the drying time is relatively low, which improves the process efficiency.
[0046] Preferably, the sealing slurry in S300 includes: 10-15 parts of 830 silica sol and 18-20 parts of spherical quartz powder; the particle size of the spherical quartz powder is 150-180 mesh.
[0047] Since the particle size of the second back layer of sand is relatively high, the sealing layer needs to have a certain thickness to cover the sand layer to ensure the surface strength of the shell.
[0048] Preferably, the drying conditions in S300 are: drying temperature of 25-30° C., relative humidity of 40%-45%, and drying time of 5-8 hours.
[0049] A silica sol shell prepared by the preparation method.
[0050] The present invention has at least the following beneficial effects:
[0051] The present invention reduces the amount of zircon powder while ensuring the coating performance and surface quality of the surface layer slurry and improving the maximum thickness of the surface layer by reducing the concentration of silica sol, compounding and grading quartz powder and zircon powder, and selecting the morphology. Experiments show that the average coating thickness can reach 0.082, and the cost is greatly reduced.
[0052] Due to the improvement of the surface layer slurry, the present invention can increase the sanding particle size of the surface layer, increase the bonding degree between the surface layer and the back layer, reduce the possibility of cracking during baking, improve the mechanical properties and fire resistance of the shell, and the air permeability of the surface layer is also better. DETAILED DESCRIPTION
[0053] In order to make the purpose, method scheme and advantages of the embodiments of the present invention clearer, the method scheme in the embodiments of the present invention is clearly and completely described. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0054] Embodiment 1: A surface slurry for preparing a silica sol shell comprises, in parts by weight: 10 parts of silica sol, 20 parts of angular quartz powder, and 5 parts of spherical zircon powder; the content of silicon dioxide in the silica sol is 26wt%, the particle size of the angular quartz powder is 180 mesh, and the particle size of the spherical zircon powder is 300 mesh.
[0055] Example 2: A surface slurry for preparing a silica sol shell, comprising, by weight: 10 parts of silica sol, 25 parts of angular quartz powder, and 8 parts of spherical zircon powder; the content of silicon dioxide in the silica sol is 26wt%, the particle size of the angular quartz powder is 180 mesh, and the particle size of the spherical zircon powder is 300 mesh.
[0056] Example 3: A surface slurry for preparing a silica sol shell, comprising, by weight: 10 parts of silica sol, 23 parts of angular quartz powder, and 7 parts of spherical zircon powder; the content of silicon dioxide in the silica sol is 26wt%, the particle size of the angular quartz powder is 180 mesh, and the particle size of the spherical zircon powder is 300 mesh.
[0057] Example 4: A surface slurry for preparing a silica sol shell, comprising, by weight: 10 parts of silica sol, 23 parts of angular quartz powder, and 7 parts of spherical zircon powder; the content of silicon dioxide in the silica sol is 26wt%, the particle size of the angular quartz powder is 200 mesh, and the particle size of the spherical zircon powder is 300 mesh.
[0058] Example 5: A surface slurry for preparing a silica sol shell, comprising, by weight: 10 parts of silica sol, 23 parts of angular quartz powder, and 7 parts of spherical zircon powder; the content of silicon dioxide in the silica sol is 26wt%, the particle size of the angular quartz powder is 200 mesh, and the particle size of the spherical zircon powder is 350 mesh.
[0059] Example 6: A surface slurry for preparing a silica sol shell, comprising, by weight: 10 parts of silica sol, 23 parts of angular quartz powder, and 7 parts of spherical zircon powder; the content of silicon dioxide in the silica sol is 26wt%, the particle size of the angular quartz powder is 200 mesh, and the particle size of the spherical zircon powder is 270 mesh.
[0060] Comparative Example 1: A surface slurry for preparing a silica sol shell, comprising, by weight: 10 parts of silica sol, 23 parts of angular quartz powder, and 7 parts of spherical zircon powder; the content of silicon dioxide in the silica sol is 30wt%, the particle size of the angular quartz powder is 200 mesh, and the particle size of the spherical zircon powder is 300 mesh.
[0061] Comparative Example 2: A surface slurry for preparing a silica sol shell, comprising, by weight: 10 parts of silica sol, 23 parts of spherical quartz powder, and 7 parts of angular zircon powder; the content of silicon dioxide in the silica sol is 26wt%, the particle size of the angular zircon powder is 200 mesh, and the particle size of the spherical quartz powder is 300 mesh.
[0062] Comparative Example 3: A surface slurry for preparing a silica sol shell, comprising, by weight: 10 parts of silica sol and 30 parts of spherical quartz powder; the content of silicon dioxide in the silica sol is 26wt%, and the particle size of the spherical quartz powder is 300 mesh.
[0063] Comparative Example 4: A surface slurry for preparing a silica sol shell, comprising, by weight: 10 parts of silica sol and 30 parts of spherical zircon powder; the content of silicon dioxide in the silica sol is 26wt%, and the particle size of the spherical zircon powder is 300 mesh.
[0064] Test 1: The surface layer slurry was prepared according to the proportions of Examples 1-6 and Comparative Examples 1-4, and the viscosity of each surface layer slurry was tested by measuring with a standard flow cup. The time for the liquid to flow out of the flow cup was used to characterize the slurry viscosity. The longer the time, the higher the viscosity. Each group of tests was repeated five times and the average value was taken. The specific test results are shown in Table 1.
[0065] Table 1
[0066]
[0067] From the test results of Examples 1-6, it can be seen that the powder-to-material ratio of the surface layer slurry can reach 3.3 while ensuring that the surface layer slurry does not affect the viscosity, which is much higher than pure quartz powder silica sol and can significantly reduce the process cost.
[0068] From the comparison between Comparative Example 1 and Example 4, it can be seen that when 830 silica sol is used without distilled water dilution and the concentration is reduced, the viscosity of the system will increase significantly.
[0069] From the comparison between Comparative Example 2 and Example 4, it can be seen that when angular zircon powder and spherical quartz powder are compounded, the viscosity of the system increases significantly when the powder ratio remains unchanged.
[0070] From the comparison between Comparative Example 3 and Example 4, it can be seen that when only spherical quartz powder is used as the refractory material, even if the content of silicon dioxide in the silica sol is reduced, when the powder-to-material ratio reaches 3.0, the slurry viscosity will seriously affect the coating.
[0071] From the comparison between comparative example 4 and example 4, it can be seen that although the present invention uses quartz powder as the main refractory material, its performance is close to that of pure zircon powder slurry, and the cost is reduced by 60-70% compared with that of pure zircon powder slurry.
[0072] Embodiment 7: A method for preparing a silica sol shell, comprising:
[0073] S100, immersing the mold into the surface layer slurry described in Example 4 for mold hanging, and then sanding and drying to obtain a surface layer mold; drying conditions: drying temperature is 20°C, relative humidity is 60%, and drying time is 15h; the surface layer is sanded with 100 mesh mullite sand.
[0074] S200, the surface layer pattern is hung in the back layer slurry, and then sanded and dried, and the process is repeated for multiple times to obtain a back layer shell mold; drying conditions: drying temperature is 32° C., relative humidity is 35%, and drying time is 7 hours;
[0075] The S200 includes:
[0076] D100, the surface layer pattern is molded in the first back layer slurry, and then sanded and dried to obtain the first back layer pattern; the first back layer slurry comprises: 15 parts of 830 silica sol and 24 parts of spherical quartz powder; the particle size of the spherical quartz powder is 220 mesh, and 120 mesh mullite sand is used for sanding;
[0077] D200, the first back layer pattern is hung in the second back layer slurry, and then sanded and dried to obtain a back layer shell mold; the second back layer slurry includes: 12 parts of 1430 silica sol and 17 parts of spherical quartz powder; the particle size of the spherical quartz powder is 160 mesh, and 40 mesh mullite sand is used for sanding.
[0078] S300, hanging the back shell mold in the sealing slurry, and demoulding after drying to obtain a primary shell mold; the sealing slurry includes: 15 parts of 830 silica sol and 18 parts of spherical quartz powder; the particle size of the spherical quartz powder is 160 mesh. Drying conditions: drying temperature is 30°C, relative humidity is 45%, and drying time is 6 hours.
[0079] S400, the primary shell mold is subjected to a calcination process to obtain a silica sol shell; the calcination process includes: firstly heating to 800°C at a rate of 15°C / min and keeping the temperature for 20 minutes, and then heating to 1050°C at a rate of 28°C / min and keeping the temperature for 30 minutes.
[0080] Embodiment 8: A method for preparing a silica sol shell, comprising:
[0081] S100, immersing the mold into the surface layer slurry described in Example 4 for mold hanging, and then sanding and drying to obtain a surface layer mold; drying conditions: drying temperature is 20°C, relative humidity is 60%, and drying time is 15h; the surface layer is sanded with 100 mesh mullite sand.
[0082] S200, the surface layer pattern is hung in the back layer slurry, and then sanded and dried, and after repeated multiple times, a back layer shell mold is obtained; drying conditions: drying temperature is 32° C., relative humidity is 35%, and drying time is 7 hours;
[0083] The S200 includes:
[0084] D100, the surface layer pattern is molded in the first back layer slurry, and then sanded and dried to obtain the first back layer pattern; the first back layer slurry includes: 15 parts of 830 silica sol and 24 parts of spherical quartz powder; the particle size of the spherical quartz powder is 220 mesh, and 140 mesh mullite sand is used for sanding;
[0085] D200, the first back layer pattern is hung in the second back layer slurry, and then sanded and dried to obtain a back layer shell mold; the second back layer slurry includes: 12 parts of 1430 silica sol and 17 parts of spherical quartz powder; the particle size of the spherical quartz powder is 160 mesh, and 40 mesh mullite sand is used for sanding.
[0086] S300, hanging the back shell mold in the sealing slurry, and demoulding after drying to obtain a primary shell mold; the sealing slurry includes: 15 parts of 830 silica sol and 18 parts of spherical quartz powder; the particle size of the spherical quartz powder is 160 mesh. Drying conditions: drying temperature is 30°C, relative humidity is 45%, and drying time is 6 hours.
[0087] S400, the primary shell mold is subjected to a calcination process to obtain a silica sol shell; the calcination process includes: firstly heating to 800°C at a rate of 15°C / min and keeping the temperature for 20 minutes, and then heating to 1050°C at a rate of 28°C / min and keeping the temperature for 30 minutes.
[0088] Embodiment 9: A method for preparing a silica sol shell, comprising:
[0089] S100, immersing the mold into the surface layer slurry described in Example 4 for mold hanging, and then sanding and drying to obtain a surface layer mold; drying conditions: drying temperature is 20°C, relative humidity is 60%, and drying time is 15h; the surface layer is sanded with 100 mesh mullite sand.
[0090] S200, the surface layer pattern is hung in the back layer slurry, and then sanded and dried, and after repeated multiple times, a back layer shell mold is obtained; drying conditions: drying temperature is 32° C., relative humidity is 35%, and drying time is 7 hours;
[0091] The S200 includes:
[0092] D100, the surface layer pattern is molded in the first back layer slurry, and then sanded and dried to obtain the first back layer pattern; the first back layer slurry comprises: 15 parts of 830 silica sol and 24 parts of spherical quartz powder; the particle size of the spherical quartz powder is 220 mesh, and 130 mesh mullite sand is used for sanding;
[0093] D200, the first back layer pattern is hung in the second back layer slurry, and then sanded and dried to obtain a back layer shell mold; the second back layer slurry includes: 12 parts of 1430 silica sol and 17 parts of spherical quartz powder; the particle size of the spherical quartz powder is 160 mesh, and 40 mesh mullite sand is used for sanding.
[0094] S300, hanging the back shell mold in the sealing slurry, and demoulding after drying to obtain a primary shell mold; the sealing slurry includes: 15 parts of 830 silica sol and 18 parts of spherical quartz powder; the particle size of the spherical quartz powder is 160 mesh. Drying conditions: drying temperature is 30°C, relative humidity is 45%, and drying time is 6 hours.
[0095] S400, the primary shell mold is subjected to a calcination process to obtain a silica sol shell; the calcination process includes: firstly heating to 800°C at a rate of 15°C / min and keeping the temperature for 20 minutes, and then heating to 1050°C at a rate of 28°C / min and keeping the temperature for 30 minutes.
[0096] Embodiment 10: A method for preparing a silica sol shell, comprising:
[0097] S100, immersing the mold into the surface layer slurry described in Example 4 for mold hanging, and then sanding and drying to obtain a surface layer mold; drying conditions: drying temperature is 20°C, relative humidity is 60%, and drying time is 15h; the surface layer is sanded with 100 mesh mullite sand.
[0098] S200, the surface layer pattern is hung in the back layer slurry, and then sanded and dried, and the process is repeated for multiple times to obtain a back layer shell mold; drying conditions: drying temperature is 32° C., relative humidity is 35%, and drying time is 7 hours;
[0099] The S200 includes:
[0100] D100, the surface layer pattern is molded in the first back layer slurry, and then sanded and dried to obtain the first back layer pattern; the first back layer slurry comprises: 15 parts of 830 silica sol and 24 parts of spherical quartz powder; the particle size of the spherical quartz powder is 220 mesh, and 130 mesh mullite sand is used for sanding;
[0101] D200, the first back layer pattern is hung in the second back layer slurry, and then sanded and dried to obtain a back layer shell mold; the second back layer slurry includes: 12 parts of 1430 silica sol and 17 parts of spherical quartz powder; the particle size of the spherical quartz powder is 160 mesh, and 40 mesh mullite sand is used for sanding.
[0102] S300, hanging the back shell mold in the sealing slurry, and demoulding after drying to obtain a primary shell mold; the sealing slurry includes: 15 parts of 830 silica sol and 18 parts of spherical quartz powder; the particle size of the spherical quartz powder is 160 mesh. Drying conditions: drying temperature is 30°C, relative humidity is 45%, and drying time is 6 hours.
[0103] S400, the primary shell mold is subjected to a calcination process to obtain a silica sol shell; the calcination process includes: firstly heating to 800°C at a rate of 20°C / min and keeping the temperature for 20 minutes, and then heating to 1050°C at a rate of 28°C / min and keeping the temperature for 30 minutes.
[0104] Embodiment 11: A method for preparing a silica sol shell, comprising:
[0105] S100, immersing the mold into the surface layer slurry described in Example 4 for mold hanging, and then sanding and drying to obtain a surface layer mold; drying conditions: drying temperature is 20°C, relative humidity is 60%, and drying time is 15h; the surface layer is sanded with 100 mesh mullite sand.
[0106] S200, the surface layer pattern is hung in the back layer slurry, and then sanded and dried, and after repeated multiple times, a back layer shell mold is obtained; drying conditions: drying temperature is 32° C., relative humidity is 35%, and drying time is 7 hours;
[0107] The S200 includes:
[0108] D100, the surface layer pattern is molded in the first back layer slurry, and then sanded and dried to obtain the first back layer pattern; the first back layer slurry comprises: 15 parts of 830 silica sol and 24 parts of spherical quartz powder; the particle size of the spherical quartz powder is 220 mesh, and 130 mesh mullite sand is used for sanding;
[0109] D200, the first back layer pattern is hung in the second back layer slurry, and then sanded and dried to obtain a back layer shell mold; the second back layer slurry includes: 12 parts of 1430 silica sol and 17 parts of spherical quartz powder; the particle size of the spherical quartz powder is 160 mesh, and 40 mesh mullite sand is used for sanding.
[0110] S300, hanging the back shell mold in the sealing slurry, and demoulding after drying to obtain a primary shell mold; the sealing slurry includes: 15 parts of 830 silica sol and 18 parts of spherical quartz powder; the particle size of the spherical quartz powder is 160 mesh. Drying conditions: drying temperature is 30°C, relative humidity is 45%, and drying time is 6 hours.
[0111] S400, the primary shell mold is subjected to a calcination process to obtain a silica sol shell; the calcination process includes: firstly heating to 800°C at a rate of 10°C / min and keeping the temperature for 20 minutes, and then heating to 1050°C at a rate of 28°C / min and keeping the temperature for 30 minutes.
[0112] Embodiment 12: A method for preparing a silica sol shell, comprising:
[0113] S100, immersing the mold into the surface layer slurry described in Example 4 for mold hanging, and then sanding and drying to obtain a surface layer mold; drying conditions: drying temperature is 20°C, relative humidity is 60%, and drying time is 15h; the surface layer is sanded with 100 mesh mullite sand.
[0114] S200, the surface layer pattern is hung in the back layer slurry, and then sanded and dried, and after repeated multiple times, a back layer shell mold is obtained; drying conditions: drying temperature is 32° C., relative humidity is 35%, and drying time is 7 hours;
[0115] The S200 includes:
[0116] D100, the surface layer pattern is molded in the first back layer slurry, and then sanded and dried to obtain the first back layer pattern; the first back layer slurry comprises: 15 parts of 830 silica sol and 24 parts of spherical quartz powder; the particle size of the spherical quartz powder is 220 mesh, and 130 mesh mullite sand is used for sanding;
[0117] D200, the first back layer pattern is hung in the second back layer slurry, and then sanded and dried to obtain a back layer shell mold; the second back layer slurry includes: 12 parts of 1430 silica sol and 17 parts of spherical quartz powder; the particle size of the spherical quartz powder is 160 mesh, and 40 mesh mullite sand is used for sanding.
[0118] S300, hanging the back shell mold in the sealing slurry, and demoulding after drying to obtain a primary shell mold; the sealing slurry includes: 15 parts of 830 silica sol and 18 parts of spherical quartz powder; the particle size of the spherical quartz powder is 160 mesh. Drying conditions: drying temperature is 30°C, relative humidity is 45%, and drying time is 6 hours.
[0119] S400, the primary shell mold is subjected to a calcination process to obtain a silica sol shell; the calcination process includes: firstly heating to 700°C at a rate of 20°C / min and keeping the temperature for 20 minutes, and then heating to 1050°C at a rate of 28°C / min and keeping the temperature for 30 minutes.
[0120] Embodiment 13: A method for preparing a silica sol shell, comprising:
[0121] S100, immersing the mold into the surface layer slurry described in Example 4 for mold hanging, and then sanding and drying to obtain a surface layer mold; drying conditions: drying temperature is 20°C, relative humidity is 60%, and drying time is 15h; the surface layer is sanded with 100 mesh mullite sand.
[0122] S200, the surface layer pattern is hung in the back layer slurry, and then sanded and dried, and the process is repeated for multiple times to obtain a back layer shell mold; drying conditions: drying temperature is 32° C., relative humidity is 35%, and drying time is 7 hours;
[0123] The S200 includes:
[0124] D100, the surface layer pattern is molded in the first back layer slurry, and then sanded and dried to obtain the first back layer pattern; the first back layer slurry comprises: 15 parts of 830 silica sol and 24 parts of spherical quartz powder; the particle size of the spherical quartz powder is 220 mesh, and 130 mesh mullite sand is used for sanding;
[0125] D200, the first back layer pattern is hung in the second back layer slurry, and then sanded and dried to obtain a back layer shell mold; the second back layer slurry includes: 12 parts of 1430 silica sol and 17 parts of spherical quartz powder; the particle size of the spherical quartz powder is 160 mesh, and 40 mesh mullite sand is used for sanding.
[0126] S300, hanging the back shell mold in the sealing slurry, and demoulding after drying to obtain a primary shell mold; the sealing slurry includes: 15 parts of 830 silica sol and 18 parts of spherical quartz powder; the particle size of the spherical quartz powder is 160 mesh. Drying conditions: drying temperature is 30°C, relative humidity is 45%, and drying time is 6 hours.
[0127] S400, the primary shell mold is subjected to a calcination process to obtain a silica sol shell; the calcination process includes: firstly heating to 800°C at a rate of 20°C / min and keeping the temperature for 20 minutes, and then heating to 1050°C at a rate of 30°C / min and keeping the temperature for 30 minutes.
[0128] Example 14: Based on Example 12, the spherical quartz powder used in the first backing layer slurry is modified quartz powder, and the preparation steps of the modified quartz powder include: adding the spherical quartz powder to the polysaccharide solution, and obtaining the modified quartz powder by spray drying. The mass concentration of the polysaccharide solution is 20%, the polysaccharide includes chitosan, and the mass ratio of the spherical quartz powder to the polysaccharide solution is 1:2.
[0129] Example 15: Based on Example 12, the spherical quartz powder used in the first backing layer slurry is modified quartz powder, and the preparation steps of the modified quartz powder include: adding the spherical quartz powder to the polysaccharide solution, and obtaining the modified quartz powder by spray drying. The mass concentration of the polysaccharide solution is 20%, the polysaccharide includes cyclodextrin, and the mass ratio of the spherical quartz powder to the polysaccharide solution is 1:2.
[0130] Example 16: Based on Example 12, the spherical quartz powder used in the first backing layer slurry is modified quartz powder, and the preparation steps of the modified quartz powder include: adding the spherical quartz powder to a polysaccharide solution, and then obtaining the modified quartz powder by spray drying. The mass concentration of the polysaccharide solution is 20%, the polysaccharide includes sodium alginate, and the mass ratio of the spherical quartz powder to the polysaccharide solution is 1:2.
[0131] Example 17: Based on Example 12, the spherical quartz powder used in the first backing layer slurry is modified quartz powder, and the preparation steps of the modified quartz powder include: adding the spherical quartz powder to a polysaccharide solution, and obtaining the modified quartz powder by spray drying. The mass concentration of the polysaccharide solution is 20%, the polysaccharide includes cellulose, and the mass ratio of the spherical quartz powder to the polysaccharide solution is 1:2.
[0132] Comparative Example 5: Except that the sand in D100 was 70 mesh, the other process steps were the same as those in Example 15.
[0133] Comparative Example 6: The roasting process in S400 includes: first heating to 800°C at a rate of 25°C / min and keeping warm for 20 minutes, then heating to 1050°C at a rate of 30°C / min and keeping warm for 30 minutes. The remaining process steps are consistent with Example 15.
[0134] Comparative Example 7: The roasting process in S400 includes: first heating to 800°C at a rate of 20°C / min and keeping warm for 20 minutes, then heating to 1050°C at a rate of 35°C / min and keeping warm for 30 minutes. The remaining process steps are consistent with Example 15.
[0135] Comparative Example 8: The roasting process in S400 includes: first heating to 800°C at a rate of 20°C / min and keeping warm for 10 min, then heating to 1050°C at a rate of 30°C / min and keeping warm for 30 min. The remaining process steps are consistent with Example 15.
[0136] Test 2: The silica sol shells prepared by the preparation methods of Examples 7-17 and Comparative Examples 5-8 were subjected to air permeability tests and high temperature strength tests. Each group of tests was tested five times and the average value was taken. The air permeability test was carried out in accordance with the standard method of JB / T 4153-1999 "High Temperature Air Permeability Test Method for Shells". The test temperature was 950°C and the air permeability unit was m 4 / (N·min). The high temperature strength is in accordance with HB5352.1-2004 "Test Methods for Properties of Investment Casting Shells Part 1: Determination of Bending Strength", the test temperature is 1300℃, and the unit of high temperature strength is MPa. The test results are shown in Table 2.
[0137] Table 2
[0138]
[0139]
[0140] It can be seen from the test results of Examples 7-17 that the silica sol shell prepared according to the preparation method of the present invention has good air permeability and high temperature strength.
[0141] From the test results of Examples 7-9, it can be seen that the air permeability is best when the particle size of the sand in D100 is 130 mesh.
[0142] From the test results of Examples 9-11, it can be seen that when the initial heating rate reaches 20°C / min during sintering, the mold shell still has good high-temperature strength and the drying time can be reduced; when the heating rate is 20°C / min, the air permeability of the mold shell is the best. When the heating rates are 15°C / min and 20°C / min, the high-temperature strength of the mold shell is equivalent.
[0143] From the comparison between Example 10 and Example 12, it can be seen that when the primary insulation temperature is 800°C, the air permeability of the mold shell is optimal.
[0144] From the comparison between Example 10 and Example 13, it can be seen that when the secondary heating rate reaches 30°C / min, the high-temperature strength of the shell will not decrease, and the drying time can be shortened.
[0145] From the comparison between Example 12 and Examples 14-17, it can be seen that the use of modified quartz powder will not significantly reduce the high-temperature strength of the mold shell, while also improving the air permeability of the mold shell, and the use of cyclodextrin polysaccharide solution is the best.
[0146] From the comparison between Comparative Example 5 and Example 14, it can be seen that when the particle size of the sand in D100 is larger than the surface layer according to the conventional process, the high-temperature strength will be greatly reduced under the same sintering conditions.
[0147] From the comparison between Comparative Examples 6-7 and Example 14, it can be seen that when the first stage heating rate and the second stage heating rate are too high during roasting, the high temperature strength of the shell will be seriously affected.
[0148] From the comparison between Comparative Example 8 and Example 14, it can be seen that when the insulation time is insufficient, the air permeability and high temperature strength of the shell are affected.
[0149] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A surface slurry for preparing a silica sol shell, characterized in that: In parts by weight, it comprises: 8-12 parts of silica sol, 20-25 parts of angular quartz powder, and 5-8 parts of spherical zircon powder; the content of silicon dioxide in the silica sol is 23wt%-27wt%, the particle size of the angular quartz powder is 180-200 mesh, and the particle size of the spherical zircon powder is 270-350 mesh.
2. A method for preparing a silica sol shell, characterized in that: include: S100, immersing the mold into the surface layer slurry according to claim 1 for mold hanging, and then sanding and drying to obtain a surface layer mold; S200, hanging the surface layer pattern in the back layer slurry, and then sanding and drying, after repeating for multiple times, to obtain a back layer shell mold; S300, hanging the back layer shell mold in the sealing slurry, and demoulding after drying to obtain a primary shell mold; S400, the primary shell mold is subjected to a calcination process to obtain a silica sol shell; The surface layer is sanded with 80-100 mesh Mullite sand.
3. The preparation method according to claim 2, characterized in that: The S200 includes: D100, the surface layer pattern is molded in the first back layer slurry, and then sanded and dried to obtain the first back layer pattern; the first back layer slurry comprises: 10-15 parts of 830 silica sol and 18-24 parts of spherical quartz powder; the particle size of the spherical quartz powder is 200-230 mesh, and 120-140 mesh mullite sand is used for sanding; D200, the first back layer pattern is hung in the second back layer slurry, and then sanded and dried to obtain a back layer shell mold; the second back layer slurry includes: 10-15 parts of 1430 silica sol and 13-17 parts of spherical quartz powder; the particle size of the spherical quartz powder is 150-180 mesh, and 40-60 mesh mullite sand is used for sanding.
4. The preparation method according to claim 3, characterized in that: The spherical quartz powder used in the first backing layer slurry is modified quartz powder. The preparation steps of the modified quartz powder include: adding the spherical quartz powder to a polysaccharide solution, and obtaining the modified quartz powder by a spray drying method.
5. The preparation method according to claim 4, characterized in that: The mass concentration of the polysaccharide solution is 15%-20%, the polysaccharide comprises one or more of chitosan, sodium alginate, cellulose and cyclodextrin, and the mass ratio of spherical quartz powder to the polysaccharide solution is 1:2-2:
3.
6. The preparation method according to claim 5, characterized in that: The calcination process in S400 includes: firstly heating to 700-800°C at a rate of 10-20°C / min and keeping the temperature for 15-25min, and then heating to 950-1050°C at a rate of 25-30°C / min and keeping the temperature for 20-30min.
7. The preparation method according to any one of claims 1 to 6, characterized in that: The drying conditions in S100 are as follows: drying temperature is 20-25°C, relative humidity is 50%-60%, and drying time is 10-15h; the drying conditions in S200 are as follows: drying temperature is 30-35°C, relative humidity is 30%-40%, and drying time is 6-8h.
8. The preparation method according to claim 7, characterized in that: The sealing slurry in S300 includes: 10-15 parts of 830 silica sol and 18-20 parts of spherical quartz powder; the particle size of the spherical quartz powder is 150-180 meshes.
9. The preparation method according to claim 8, characterized in that: Drying conditions in S300: drying temperature is 25-30°C, relative humidity is 40%-45%, and drying time is 5-8h.
10. A silica sol shell obtained by the preparation method according to any one of claims 2 to 9.
Citation Information
Patent Citations
Investment precoat for making shell in investment casting
CN104190861A
Investment casting shell coating and method for manufacturing shell surface with same
CN105710287A
Near-zero shrinkage rate molding shell based on fused quartz and preparation method thereof
CN105903901A
Manufacturing process of silica sol mould shell
CN108044034A
Preparation method of mold shell of K403 high temperature alloy nozzle ring casting
CN108994258A